2023
DOI: 10.1177/00033197221150953
|View full text |Cite
|
Sign up to set email alerts
|

Association of Coronary Artery Severity and Late In-Stent Restenosis: An Angiographic Imaging Study

Abstract: Coronary in-stent restenosis (ISR) remains a challenge in interventional cardiology. We investigated the relationship between angiographic pre-interventional grade of lesion stenosis (LS) and the prognosis of late ISR. After exclusions, 110 patients with ISR and 109 patients without ISR were compared. In the ISR group, the grade of LS was greater ( P < .001) and the length of the critical segment (LCS) was longer ( P < .001). Stent length was longer in the ISR group ( P = .008). Compared with the LCS, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…Lately, researchers observed that patients who developed lesions in different vessels were vulnerable to ISR [18]. The degree of C-reactive protein is a novel biomarker of ISR supported by several evidences (19). Additionally, hereditary polymorphism may be a capability in the progress of ISR, as studies have shown that some SNPs in CD18 and MMP13 genes increase the risk of ISR (20).…”
Section: Discussionmentioning
confidence: 99%
“…Lately, researchers observed that patients who developed lesions in different vessels were vulnerable to ISR [18]. The degree of C-reactive protein is a novel biomarker of ISR supported by several evidences (19). Additionally, hereditary polymorphism may be a capability in the progress of ISR, as studies have shown that some SNPs in CD18 and MMP13 genes increase the risk of ISR (20).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, considering the millions of DES implants each year, ISR remains a huge challenge. 5 COPD is a slowly progressing lung disease that trigger systemic inflammation. The mortality rate of this disease is high.…”
Section: Introductionmentioning
confidence: 99%